Multicultural Counselling Competencies with Female Adolescents: A Qualitative Investigation of Client Experiences - Kassan, Anusha; Sinacore, Ada L. (Canadian Journal of Counselling and Psychotherapy, 2016)
As the cultural landscape of North America continues to shift, the helping profession is tasked with the responsibility of delivering culturally sensitive services. This phenomenological study explored the experiences of young women who attended counselling during their adolescence. Using a multicultural counselling competency framework as well as an inclusive definition of multiculturalism, the central phenomenon under investigation was that of participants’ perceptions of their counsellors’ cultural competence. Results demonstrated that counsellor awareness, knowledge, skills, and the multicultural counselling relationship are important competencies when working with female adolescents. Additional meaningful themes included cultural sensitivity, family interventions, and help beyond counselling. Implications for training and practice are discussed.